Cassava varietal dissemination in Vietnam - Hoang, Kim; Tran, Ngoc Quyen; Pham, Van Bien; Kawano, Kazuo (International Center for Tropical Agriculture, 1998)
Before 1985, Gon, H34 and Xanh Vinh Phu were the most popular cassava varieties in Vietnam. From 1986 to 1993, HL20, HL23 and HL24 were selected from the local variety collection by Hung Loc Agricultural Research Center (HARC) and were grown extensively in South Vietnam with annual areas of about 70,000 to 80,000 ha planted to these varieties. More recently (1993-1996) the Vietnam Root Crops Program in cooperation with CIAT, selected and recommended two new cassava varieties, KM60 (Rayong 60) and KM94 (MKUC 28- 77-3); these were recognized and released for production by the Ministry of Agriculture and Rural Development (MARD). The two varieties are now widely grown in an area of about 15,000 ha in 1996.